1296 DEMOGRAPHIC AND MORTALITY EVALUATION OF URGENT COMMUNITY RESPONSE REFERRALS THAT ARE MANAGED IN COMMUNITY VS THOSE HOSPITALISED. (16th January 2023) - Tayler-Gray, J; Patel, M; Wigley, A; McCall, B; Gossage, J
Abstract: Introduction: Demographic evaluation of urgent community response teams [UCR] is important to ensure equity of access and clinical outcomes for patients from all socio-demographic groups using such services. This retrospective descriptive study aimed to evaluate demographic and mortality differences between patients referred to UCR in terms of those managed in the community [Group1] versus those subsequently hospitalised [Group2]. Methods: Data was obtained over a 12-month period [2021-2022] for all new patients referred to a 7-day consultant-led UCR that serves a multi-ethnic, inner-city population. Data included demographic details, source of referral, urgency of referral and mortality within 60 days. Results: Of 995 patients, 75.6%[n=752] were in Group 1; 24.4%[243] were in Group 2. The two groups were comparable in terms of age [mean(SD): 80.1(12.6) vs 80.0(11.4), p=ns] and gender [males:39.4% vs 42.4%, p=ns]. There were similar proportion of Black and minority ethnic patients within the two groups [21.0% (158) vs 24.7% (60), p=ns]. Source of referral were comparable between the two groups[p=ns]; overall, 67.7%[674] were from GP practices, 5.6%[56] Community Practitioners, 4.7%[47] NHS111, 2.7%[27] Ambulance, 32%[32] Palliative care, 5.9%[59] Emergency department, 10.1%[100] post-hospitalisation. Compared to Group 1 [46.9% (353)], significantly more patients in Group 2 were referred for urgent assessment within 2 hours [65.4% (159), p<0.001]. More patients died in Group2 within 60 days [22.2% (54) vs 11.3% (85), p<0.001]. Discussion: This large survey has described age, gender and ethnic similarities between the two groups, demonstrating equity of provision irrespective of protected characteristics. As might be clinically expected, patients referred for hospitalisation were assessed more urgently and had higher mortality rates compared to those managed in the community. This study provides valuable information for clinicians and researchers of similar UCR services in future.